2013
DOI: 10.1159/000348651
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Levels of Circulating Adipokines and Adiponectin/Resistin Index with Carotid Intima-Media Thickness in Hypertensive Type 2 Diabetic Patients

Abstract: Background: Hypoadiponectinemia and hyperresistinemia are associated with cardiovascular disease. The increase in the carotid intima-media thickness (CIMT) assessed by B-mode ultrasound has been directly associated with increased risk of myocardial infarction and stroke. Objective: To evaluate the correlation between adipokine levels with CIMT in hypertensive type 2 diabetic patients. Methods: Serum levels of adiponectin and resistin levels were measured by ELISA in 30 type 2 diabetic patients with never-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Prior studies have shown resistin to be linked to both endothelial and cardiomyocyte dysfunction, as well as alterations in cholesterol metabolism. Accordingly, the association of resistin with subclinical atherosclerosis has been illustrated by its relationship to elevated coronary artery calcium levels 11 and increased carotid intima-media thickness 37 . Our study extends beyond subclinical atherosclerosis and focuses in on CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown resistin to be linked to both endothelial and cardiomyocyte dysfunction, as well as alterations in cholesterol metabolism. Accordingly, the association of resistin with subclinical atherosclerosis has been illustrated by its relationship to elevated coronary artery calcium levels 11 and increased carotid intima-media thickness 37 . Our study extends beyond subclinical atherosclerosis and focuses in on CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has shown that the levels of VCAM-1 correlate with the severity of albuminuria in diabetic hypertensive patients [15] . In addition, Seron et al [16] reported that VCAM-1 expression is increased in kidney biopsies from patients with DN, they also found a correlation between levels of VCAM-1 and numbers of infiltrating immune cells [18] .…”
Section: Adhesion Moleculesmentioning
confidence: 97%
“…It is also important to note that our patients were naive to thiazolindinedione, statin and angiotensin-converting enzymes/angiotensin II receptor blockers, because these drugs have been shown to modify circulating levels of adipocytokines (1).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the role of hypoadiponectinemia and hyperresistinemia in the development of insulin resistance and in the pathways that lead to atherosclerosis, both adipocytokines are potential treatment targets. In fact, increasing adiponectin and reducing resistin levels contribute to reducing the risk for cardiovascular disease (1,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation